2015
DOI: 10.1007/s00268-015-2947-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Retropharyngeal Node Metastases from Thyroid Carcinoma

Abstract: Management of RPN is not always surgical. Discussion of options in a multidisciplinary tumor board setting may optimize care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…2 In 2015, Hartl et al completed a systematic review of the literature regarding the management of RP metastases of thyroid carcinoma and reported five additional cases. 3 They concluded that, while surgical management is most common, other nonsurgical treatment options exist and may be appropriate in certain cases. 3 Although they could not definitively determine risk factors due to the lack of consistency in the reported data, they determined that RP metastases were often associated with tumors classified as pN1b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In 2015, Hartl et al completed a systematic review of the literature regarding the management of RP metastases of thyroid carcinoma and reported five additional cases. 3 They concluded that, while surgical management is most common, other nonsurgical treatment options exist and may be appropriate in certain cases. 3 Although they could not definitively determine risk factors due to the lack of consistency in the reported data, they determined that RP metastases were often associated with tumors classified as pN1b.…”
Section: Discussionmentioning
confidence: 99%
“…18 Malignancies in the RP and PP spaces may represent either primary tumors or direct extension of nearby tumors, metastatic lymph nodes, lymphoproliferative diseases, and tumors of salivary or neurogenic origin, among others. 3,11,13,17,19 In general, the mechanism of metastatic spread of disease to the RP and PP regions is not well understood due to the inaccessibility of this region, the rarity of the presentation, and the limited available clinical data. 13 Metastases to RP nodes are most commonly associated with primary carcinomas arising in the nasopharynx, followed by the oropharynx, hypopharynx, and cervical esophagus.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Complications such as hematoma, paralysis of soft palate, temporary aspiration and difficulty in swallowing, and dysphagia are documented after surgery. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…
We read with interest the article titled, 'Management of retropharyngeal node metastases from thyroid carcinoma' by Hartl et al [1]. We congratulate the authors on addressing the issue of Retropharyngeal lymph node metastasis in thyroid cancer in the era of PET scan, with the advent of which there has been an increase in the incidence of detection of recurrences and also there is an increasing dilemma for the knife happy Endocrine surgeon as to whether wait and watch or to intervene.
…”
mentioning
confidence: 99%